Toxic Relationship as a Reason for Divorce Analysis of Judges' Decisions in the Religious Court of Jember from the Perspective of Islamic Law - Agustin, Rina Ayu; Busriyanti, Busriyanti; Sa’adah, Sri Lumatus (MultiTech Publisher, 2024)
Toxic relationship is an unhealthy relationship or toxic relationship and arguably a small problem that if it continues will result in divorce and has an uncomfortable factor between one party, as evidenced in the decision in the Jember Religious Court the subject matter in a case begins with a Toxic Relationship, indeed in the term of the judge's decision does not use the word Toxic Relationship, but if explained in detail the things that Toxic means are in accordance with the characteristics in the subject matter. researchers have a focus of study including what factors influence Toxic Relationship, the judge's consideration in deciding the case and the perspective of Islamic law regarding divorce due to Toxic Relationship. The With normative research that focuses on laws and judge decisions and type of research used by researchers is Content Analysis (Content Analysis) and the method of collecting data on the law in the form of marriage laws, KHI, legal journals and judges' decisions. Then strengthened with the perspective of Islamic law as an analysis knife in Toxic Relationship. The conclusion in a toxic relationship will be fatal if it is not supported by the family and based on strong faith, especially to the husband who is basically the head of the household.